Makna Sosial Dan Simbolik Tradisi Atolong Di Pulau Bawean Dalam Perspektif Sosiosemiotik - Amriyah, Siti; Rahmawati, Luna Rindi; Kaanubun, Caroline Maria Desi; Haerussaleh, Haerussaleh (Jurnal Pendidikan Bahasa dan Sastra Indonesia Metalingua, 2025)
The tradition of atolong is a practice of mutual cooperation that is still preserved on Bawean Island, Gresik, East Java, in weddings and funerals. This tradition represents the spirit of togetherness and cultural identity of the Bawean community. This study aims to describe the form of implementation and socio-symbolic meaning of atolong through a sociosemiotic perspective. The study uses a qualitative descriptive approach with in-depth interviews, participatory observation, and documentation in Tambak and Sangkapura subdistricts. Data analysis was conducted using Charles Sanders Peirce's semiotic theory (icon, index, symbol) combined with a socio-semiotic approach to interpret the meaning of signs in a socio-cultural context. The results show four forms of assistance, namely labor, knowledge, money, and goods. Symbols such as yellow rice, tetebbhuen, ongkek, pelangki, and rabis are interpreted as prayers for safety, warding off evil, fertility, and social recognition. These findings confirm that the tradition of atolong strengthens social solidarity, preserves cultural identity, and balances pre-Islamic values with Islamic teachings.